1995
DOI: 10.1039/c39950001137
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of phosphotriesters promoted by a zinc(II) complex bearing an alcohol pendant

Abstract: A polyamine-zinc(ii) complex with an alcohol pendant promotes the hydrolysis of diethyl(4-nitropheny1)phosphate via transfer of the diethylphosphate group to its alkoxy pendant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…It was interesting to note that a sigmoidal rate profile was obtained for both of the cases, suggesting a definite pH dependence on phosphodiester bond cleavage (Figures 6 and 7). Similar profiles have been previously reported in the literature for phosphate ester hydrolysis promoted by Cu 2 , [14] Zn 2 , [15] and Co 3 [16] complexes. As proposed in these reports, a sigmoidal rate profile is indicative of a hydrolytic mechanism, mediated by a metalhydroxy or a metal-alkoxy intermediate, rather than a radicalinduced cleavage.…”
Section: Resultssupporting
confidence: 77%
“…It was interesting to note that a sigmoidal rate profile was obtained for both of the cases, suggesting a definite pH dependence on phosphodiester bond cleavage (Figures 6 and 7). Similar profiles have been previously reported in the literature for phosphate ester hydrolysis promoted by Cu 2 , [14] Zn 2 , [15] and Co 3 [16] complexes. As proposed in these reports, a sigmoidal rate profile is indicative of a hydrolytic mechanism, mediated by a metalhydroxy or a metal-alkoxy intermediate, rather than a radicalinduced cleavage.…”
Section: Resultssupporting
confidence: 77%
“…Kady et al [31] found that mononuclear Zn II models with N 3 and N 3 O ligands showed k obs values of between 4.5 î 10 À2 and 1.5 î 10 À6 s À1 for diethyl(4-nitrophenyl)phosphate hydrolysis in water. Itoh et al [32] studied the catalytic hydrolysis of 2,4-dinitrophenyl ethylphosphate using mononuclear Cu II complexes with N 3 ligands.…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…All these reactions were investigated in solvents of much higher polarity than ours, and a very high influence of solvent polarity, for example, for the hydrolysis of 6 b, [37,54] was found for them, as it was found here for the hydrolysis of 6 d. Taking this into consideration it must be concluded that the [Tp'ZnÀOH] complexes are indeed powerful nucleophiles. Their hydrolytic activity is surpassed significantly only by that of bifunctional [57] or bimetallic [58] reagents. The reason for their nucleophilic strength must be the fact that the corresponding [Tp' ZnÀOH 2 ] complexes have very low pK a values [44,53] resulting in the existence of [Tp'ZnÀOH] as such under neutral conditions, with their ZnÀOH functions being available without assistance by a base.…”
Section: Measurementsmentioning
confidence: 93%